Comparison of five commercial anti-SARS-CoV-2 total antibodies and IgG immunoassays after vaccination with BNT162b2 mRNA - Danese, Elisa; Montagnana, Martina; Salvagno, Gian Luca; Gelati, Matteo; Peserico, Denise; Pighi, Laura; De Nitto, Simone; Henry, Brandon M.; Porru, Stefano; Lippi, Giuseppe (Journal of Medical Biochemistry, 2021)
Background. Since universal vaccinations represents the most effective strategy to mitigate coronavirus disease 2019 (COVID-19), baseline assessment and post-vaccine monitoring of anti-SARS-CoV-2 neutralizing antibodies are essential to vaccination programs. Therefore, this study aimed to compare data of five commercial anti-SARS-CoV-2 immunoassays after administration of BNT162b2 mRNA Covid-19 vaccine.Methods. Venous blood was collected from three healthcare workers, receiving a double (30 μg) dose of Comirnaty, on the day of the first vaccine dose and then at fixed intervals for the following 2 months. Anti-SARS-CoV-2 neutralizing antibody response was assayed with Roche Total Ig anti-RBD, DiaSorin IgG anti-S1/S2, Beckman Coulter IgG anti-RBD, SNIBE IgG anti-RBD and Technogenetics IgG anti-N/S1.Results. A total number of 45 samples were drawn at the end of the 2-month study period. The Spearman’s correlations of absolute anti-SARS-CoV-2 antibodies were always excellent (all p
Keywords: Antibody response; BNT162b2 mRNA vaccination; IgG